Souvenirs entomologiques de Jean-Henri Fabre : des « ailes de l’imagination » aux « sandales des faits observés » - Ringuedé, Yohann (Studia Romanica Posnaniensia, 2018)
Jean-Henri Fabre made numerous discoveries observing meticulously the lifestyle and behaviour of insects which lived around his traditional house in Provence. Those discoveries are still valid, even though the heterodox entomologist became the standard bearer for opponents of transformism, which perpetually progressed and is about to triumph. Fabre is first known to have been an outstanding observer, but also to have gathered together in a colossal collection his entomologist’s memoirs, whose literary – and even poetic – value is celebrated as far away as Japan. This article proposes to question the validity of the preconceived idea that Les Souvenirs entomologiques adds to the accurate eye of the observer the fertile imagination of the poet. Refusing to just make note of this a posteriori superposition, it hypothesizes that there is a reunification of the inflexible empiricism of the biological approach with a creative imagination which reveals to be omnipresent in every phase of Fabre’s enterprise: the hypothesis, the validation by observation, and the literary transcription.